2019
DOI: 10.5539/elt.v12n6p191
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Using YouTubes and Audio Tracks Imitation YATI on Improving Speaking Skills of EFL Learners

Abstract: The purpose of this study is to shed light on a developed approach to be adopted in EFL speaking classes and show the effectiveness of using YouTube videos and Listening Audio Tracks Imitation (YATI) for teaching English language in speaking classrooms as pedagogical tools to improve EFL learners’ speaking skills. To find out the impact of using You Tubes and Audio Tracks Imitation (YATI) on improving speaking skills of EFL learners, the qualitative experimental approach is used to conduct this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 8 publications
2
25
0
Order By: Relevance
“…The first factor is vocabulary mastery. Lack of vocabulary along with the inability to pick up the tone and intonation puts a big difficulty to the nonnative speaker (Hamad, Metwally, & Alfaruque, 2019). For some students who live in countries where English is not their first language, they do not find native speakers around them who at least help them in gaining new vocabulary, as well as learning by themselves or in learning centers or schools.…”
Section: Introductionmentioning
confidence: 99%
“…The first factor is vocabulary mastery. Lack of vocabulary along with the inability to pick up the tone and intonation puts a big difficulty to the nonnative speaker (Hamad, Metwally, & Alfaruque, 2019). For some students who live in countries where English is not their first language, they do not find native speakers around them who at least help them in gaining new vocabulary, as well as learning by themselves or in learning centers or schools.…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that mobile application experiences significantly impacted the students' language acquisition by lowering EFL speaking anxiety. Besides, the previous study by Hamad et al (2019) investigates the impact of using Youtube and audio tracks imitation on improving speaking skills of EFL learners. The results revealed that using Youtube and audio tracks imitation has a positive impact on the effectiveness of the speaking skills, fluency, and pronunciation of EFL learners.…”
Section: Figure 1 Learn English Conversation Applicationmentioning
confidence: 99%
“…It is in line with a study by Al-sobhi & Preece (2018) that mention that most Arab students find difficulty in communicating freely in English due to certain factors such as students' limited knowledge of English language, lack of confidence and motivation. Additionally, Hamad, Metwally, & Alfaruque (2019) state that body language, the right pronunciation of English letters, intonation, confidence, and correct usage of vocabulary is always a problem that is faced by both teachers and learners. Meanwhile, Machmud & Abdulah (2018) state that one problem that often appears in EFL instructions in Indonesian Schools, especially teaching a speaking skill, is the limited time allocation.…”
Section: Introductionmentioning
confidence: 99%
“…The uploaded videos can be edited in such a way that it results in a more interesting and informative content. Through this interesting content, the level of students' participation in teaching-learning English processes improves (Hamad, Metwally, & Alfaruque, 2019).…”
Section: Introductionmentioning
confidence: 99%